2018
DOI: 10.1186/s12866-018-1246-0
|View full text |Cite
|
Sign up to set email alerts
|

The variation profile of intestinal microbiota in blunt snout bream (Megalobrama amblycephala) during feeding habit transition

Abstract: BackgroundThe blunt snout bream (Megalobrama amblycephala) is one of the most important commercial herbivorous fish in China, and dietary transition is an important event in blunt snout bream development. Gut microbiota has a vital role to host animal. However, little was known about the relationship among feeding habits transition, gut microbiota and digestive enzymes of gut content.ResultsIn this study, 186,328 high-quality reads from nine 16S rRNA libraries were obtained using the Illumina MiSeq PE300 platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 67 publications
(69 reference statements)
3
9
0
Order By: Relevance
“…In regards to metabolic pathways, the predictive functions of gut microbes in the present studies agree with previous findings that they are mainly associated with the metabolism of carbohydrates, amino acids, energy and to a lesser extent lipids ( Liu et al, 2016 ; Dehler, Secombes & Martin, 2017 ; Lyons et al, 2017 ; Wei et al, 2018 ; Yildirimer & Brown, 2018 ). Actinobacteria, such as Corynebacterium and Gordonia ( Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In regards to metabolic pathways, the predictive functions of gut microbes in the present studies agree with previous findings that they are mainly associated with the metabolism of carbohydrates, amino acids, energy and to a lesser extent lipids ( Liu et al, 2016 ; Dehler, Secombes & Martin, 2017 ; Lyons et al, 2017 ; Wei et al, 2018 ; Yildirimer & Brown, 2018 ). Actinobacteria, such as Corynebacterium and Gordonia ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The predictive function of the gut microbiome of fish has only been investigated in a small handful of studies ( Lyons et al, 2017 ; Wei et al, 2018 ; Yang et al, 2019 ; Piazzon et al, 2019 ; Qiao et al, 2020 ; Piazzon et al, 2020 ) and to our knowledge this is one of the first investigations of gilthead sea bream. The absence of significant effects of diet or gut section indicate that replacing FO with CO did not drastically alter the composition and function of microbes in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to metabolic pathways, the predictive functions of gut microbes in the present studies agree with previous findings that they are mainly associated with the metabolism of carbohydrates, amino acids, energy and to a lesser extent lipids (Liu et al, 2016;Dehler, Secombes & Martin, 2017;Lyons et al, 2017;Wei et al, 2018;Yildirimer & Brown, 2018). Actinobacteria, such as Corynebacterium and Gordonia (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…According to FishBase (http://www.fishbase.org), there are approximately 33,700 fish species on Earth, accounting for over half of the total number of vertebrate species. The fish digestive tract houses many diverse microorganisms, including bacteria, archaea and fungi, which jointly create a complex microbial ecosystem (Wei et al., 2018). It has been reported that the population density of microbiomes in the marine fish gut is within the range of 10 7 –10 8 cells per gram (Izvekova et al., 2007), suggesting that a vast hidden diversity of microbiomes resides in this habitat.…”
Section: Introductionmentioning
confidence: 99%